Letters as a School of the Christian Exegesis. A Study of the Selected Early Christian Latin Letters of the 4th and 5th Century (Augustine, Jerome, and Paulinus of Nola) - Wysocki, Marcin (Verbum Vitae, 2023)
Letters are often treated as a secondary literary genre, serving only to convey information and maintain relationships between people. But Christianity, which has been called the religion of the book, can also be described as the religion of the letter. In fact, from the very beginning, it was mainly through the letters (e.g., of Paul the Apostle) that the faith and the doctrinal, moral, and disciplinary instructions were transmitted. Of course, the authors of the early Christian letters also referenced biblical themes and the Bible itself. Following the ancient rules of rhetoric, they also implemented the postulate of didacticism (docere) by making the Scriptures and their exegesis more widely known. This article aims to show how this postulate is put into practice in Latin letters written by three great patristic figures: Saint Augustine, Saint Jerome, and Saint Paulinus of Nola, the most important representatives of the golden patristic age. These outstanding early Christian pastors and writers are considered to have created a kind of “virtual school” of biblical exegesis in their letters. This article presents how this “school” functioned, from the invitation to participate, through the methods and the study program, to the praise that good students earned. It can be an excellent model for our current age, marked by online education. This can also be applied to biblical studies and the study of biblical and patristic exegesis.